An efficient gain-flattened C-band Erbium-doped fiber amplifier - Harun, Sulaiman Wadi; Rahman, Faidz Abd; Dimyati, Kaharudin; Ahmad, Harith (John Wiley & Sons, 2013)
An efficient gain-flattened C-band Erbium-doped fibre amplifier is demonstrated using a double-pass configuration with an IsoGain™ Erbium-doped fibre (EDF). The amplifier utilizes a double-propagation of signal provided by an optical circulator at the output end of the EDF to obtain an improved flat-gain characteristic. At input signal power of -10 dBm, a flat-gain of 25 dB was obtained from wavelength region from 1528 to 1568 nm. This amplifier has the potential to be used in the high channel count dense wavelenght division multiplexing system because of its simplicity and low cost. A graph is presented. Comparison of gain and noise figure between single-pass and double-pass amplifiers.